(untitled) (Modern education and development, 2025)
The article presents information about the methods and stages of development of data intelligence analysis, which allows using modern technologies to effectively analyze data and extract useful knowledge from it, and how the updating of technologies and methods helps to make the analysis more accurate and effective. With new technologies and innovations, the application will be further expanded, and it will be possible to achieve effective results in various aspects of life around the world.